An Interactive Online Approach to Teaching Evidence‐Based Dentistry with Web 2.0 Technology. Issue 8 (1st August 2017) - Zheng, Meixun; Bender, Daniel; Reid, Laura; Milani, Jim
Abstract : At many dental schools, evidence‐based dentistry (EBD) is taught in a traditional lecture format. To avoid the constraints of lectures, in 2012 the EBD unit was redesigned for online delivery at the Arthur A. Dugoni School of Dentistry at the University of the Pacific with a Web 2.0 tool called Voicethread. The aim of this study was to assess the impact of Voicethread‐based online learning on students' perceptions of learning EBD, their participation and engagement, and their acceptance of this new online delivery approach. Students' perceptions were collected from two sources: a self‐assessment quiz and a question on their self‐reported preparedness in EBD from the 2014 American Dental Education Association (ADEA) Survey of Dental School Seniors. The Voicethread analytics tool provided data on students' participation and engagement. Students' responses to the survey questions on the self‐assessment quiz provided data on their acceptance of Voicethread‐based learning. The average score of the 124 students (91% of total) taking the quiz was 7.3 out of 8. The percentage of students who reported in the 2014 ADEA survey that they were "well prepared" in EBD was 45.2%, compared with the national average of 31.2%. Responses to this question for the Classes of 2013 and 2015, who received instruction in the traditional lecture format, were 35.2% and 34.6%, respectively. With Voicethread, students actively participated and interacted with their peers through questions and answers. They perceived Voicethread to be more effective than other delivery approaches and reported that it made learning more active and engaging. These findings suggest that Voicethread may be an effective tool for students to learn EBD since it adds interactivity to online learning.